2011
DOI: 10.1007/s10396-011-0308-9
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evaluation of portal venous pulsatile flow synchronized with heartbeat intervals

Abstract: Blood flow in the portal vein is pulsatile and influenced by both the inferior vena cava and the arterial system in a complex manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 12 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…We previously showed that blood flow in the portal vein was pulsatile, showing a pattern similar to that of the inferior vena cava, as well as a pattern similar to that of the arterial system [1]. Our results suggested that pulsatile flow in the portal vein was derived from flow in the inferior vena cava (right-heart system) and arteries (left-heart system).…”
Section: Introductionmentioning
confidence: 57%
See 4 more Smart Citations
“…We previously showed that blood flow in the portal vein was pulsatile, showing a pattern similar to that of the inferior vena cava, as well as a pattern similar to that of the arterial system [1]. Our results suggested that pulsatile flow in the portal vein was derived from flow in the inferior vena cava (right-heart system) and arteries (left-heart system).…”
Section: Introductionmentioning
confidence: 57%
“…6). Similar time courses of pressure and flow are characteristics of arterial flow [1]. Portal venous flow before clamping of the mesenteric artery was characteristic of arteries.…”
Section: Clamping Of the Mesenteric Arterymentioning
confidence: 71%
See 3 more Smart Citations